Converged Radio, Youth and Urbanity in Africa Emerging trends and perspectives - Tsarwe, Stanley; Chiumbu, Sarah (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book explores the convergence of urban radio with digital media technologies in Africa, focusing on how youth are riding on the rapid (though uneven) internet rollout on the continent to participate and drive the production and consumption of urban radio. With thirteen original chapters, the book sheds new light on the changing landscape of radio in a diverse set of African countries, illustrated with rich case studies from Zimbabwe, South Africa, Eswatini, Nigeria and Kenya. This book covers the following themes: youth agency and cultural power; civic engagement and political participation; youth, identity and belonging; youth cultural expressions as well as the impact of capitalist imperatives on commercial radio programing in Africa. Vibrant and innovative, Converged Radio, Youth and Urbanity in Africa reveals the creation of a new public sphere, through which African youth project their voices and identities, participating in and shaping national discourse. Stanley Tsarwe (PhD Rhodes University) lectures Journalism at the University of Zimbabwe. He is a Senior Research Associate in the Faculty of Humanities with University of Johannesburg. His research interests are at the intersection between smart phones, the internet and talk radio. Prof Sarah Chiumbu is Associate Professor in the Department of Communication and Media in the School of Communication, University of Johannesburg, South Africa. Her research interests are in media, democracy, citizenship and representation. .
Chapter 1. Introduction: Converged radio in Africa -- Chapter 2. New wine in old wineskins? Podcasting and elite youthful voices in Southern Africa -- Chapter 3. Converged Youth Radio as a Social Mission: The role of radio among marginalised youth communities in Zimbabwe. Chapter 4. Campus Radio in the Digital Era: The case of UNESWA FM -- Chapter 5. Social Media Integration in South Africa's Western Cape Community Radio Stations: A case study of Zibonele FM, Bush Radio and Radio Tygerberg -- Chapter 6. Misunderstanding Youth Engagement: The role of commercial youth radio in promoting democracy -- Chapter 7. Radio as Self-Expression and the Limits of Public Debate -- Chapter 8. Between Social Media Virality and Radio Virality: Nigerian youth's preferred medium of participation in national discource. Chapter 9. An Alternative Arena for 'Communities of Resistance'? Podcasting, democratic spaces and counterpublics in Zimbabwe -- Chapter 10. The Influence of Radio Programmes on Youth Empowerment in Abeokuta Metropolis: A case study of Ogbc 2 90.5 FM's Asiko Awon youth -- Chapter 11. Youth, Converged Radio and Participatory Politics in Zimbabwe: The case of young adults in Harare. Lazarus Sauti and Tendai Makaripe -- Chapter 12. Radio on Web and Mobile Platforms: Increased youth participation and practices?. Chapter 13. 'Mobile Radio' and Youth Identity Formation in Harare -- Chapter 14. The Language of Audience Engagement in Converged Radio through Facebook and Twitter: A case of NRG Radio and Ghetto Radio in Nairobi, Kenya -- Chapter 15. Strategic Diversion and Commercial Exploitation: The dumbing down of youth radio programming in Zimbabwe -- Chapter 16. Urban Community Radio and the Making of Apolitical Youth: Ethiopia in Focus.
Keywords: Radio broadcasting; Internet -- Social aspects; Digital media; Ethnology -- Africa; Culture; Radio; Internet Studies; Digital and New Media; African Culture